2012
DOI: 10.1021/ja309476x
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Crystalline GaAs on Liquid Gallium Electrodes in Aqueous Electrolytes

Abstract: Crystalline GaAs (c-GaAs) has been prepared directly through electroreduction of As(2)O(3) dissolved in an alkaline aqueous solution at a liquid gallium (Ga(l)) electrode at modest temperatures (T ≥ 80 °C). Ga(l) pool electrodes yielded consistent electrochemical behavior, affording repetitive measurements that illustrated the interdependences of applied potential, concentration of dissolved As(2)O(3), and electrodeposition temperature on the quality of the resultant c-GaAs(s). Raman spectra indicated the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 73 publications
4
49
0
Order By: Relevance
“…In fact, no voltammetric feature suggestive of a mass-transport-limited reduction of HAsO 3 2− was seen out to the cathodic window edge of water. Still, at potentials more negative than −1.2 V, the onset of current for H 2 evolution was consistently larger in the presence of dissolved As 2 O 3 than 14,22 and solid metal electrodes. 23 Both in the absence and presence of dissolved As 2 O 3 , the voltammetric responses included a sharp symmetrical wave near −1.15 V that was followed by two anodic features on the return sweep near −1.1 V (Figure 1) that showed a linear dependence with scan rate (Supporting Information, Figure S1a,b).…”
Section: ■ Experimental Sectionmentioning
confidence: 87%
“…In fact, no voltammetric feature suggestive of a mass-transport-limited reduction of HAsO 3 2− was seen out to the cathodic window edge of water. Still, at potentials more negative than −1.2 V, the onset of current for H 2 evolution was consistently larger in the presence of dissolved As 2 O 3 than 14,22 and solid metal electrodes. 23 Both in the absence and presence of dissolved As 2 O 3 , the voltammetric responses included a sharp symmetrical wave near −1.15 V that was followed by two anodic features on the return sweep near −1.1 V (Figure 1) that showed a linear dependence with scan rate (Supporting Information, Figure S1a,b).…”
Section: ■ Experimental Sectionmentioning
confidence: 87%
“…GaAs ec-LLS. That is, the Ga electrode began to change its visible hue (to yellow) within the first 10 minutes of GaAs ec-LLS [15] while in GaSb ec-LLS the Ga electrode appeared unchanged for up to 30…”
Section: Comparing and Contrasting Gasb And Gaas Ec-llsmentioning
confidence: 99%
“…An important difference between Sb and As is the fact that the former is approximately 10 5 times more soluble in Ga than the latter, as determined from the corresponding phase diagrams extrapolated to the temperatures explored here. [15,[33][34][35] The difference in the equilibrium solubility has several consequences. First, the greater solvating power of Ga towards Sb 0 means that a larger absolute concentration is needed to reach supersaturation for GaSb as compared to GaAs.…”
Section: Comparing and Contrasting Gasb And Gaas Ec-llsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] By using liquid metals as the working electrode in an electrodeposition process, we have shown that electrochemically controlled semiconductor crystal growths are possible. [9][10][11][12][13] By using liquid metals as the working electrode in an electrodeposition process, we have shown that electrochemically controlled semiconductor crystal growths are possible.…”
mentioning
confidence: 99%